Wanita Bekerja, Antara Karir Dan Keluarga - Lili Hidayati (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2023)
Women are men's partners, their presence has a very important role. Not only in a household but also in all lines of life. The wheels of the economy, government, health and so on cannot be separated from the influence and role of women. However, the discussion about the role of women in human life never stops. Between the two sides never stop debating it. Men feel more superiority while women feel they have equal abilities.